The Utilization of Common Property Resources and Sustainable Management: A Case Study of Dobhan VDC of Palpa - Bhushal, Shiva Lal (Tribhuvan University Journal, 2010)
Traditional western economic approaches recognize and focus only two types of property, public and individual. But there is third dimension of property as common property resources (CPRs), which have been traditionally recognized by the society in Nepal. They are playing a crucial role in people's survival and community development particularly in rural Nepal. The common property resources can be recognized in two types viz, Natural property and Men made property. The nature and types of these properties vary from place to place and from one community to another. Each community has its own tradition and practices in utilization and management of CPRs based on their indigenous knowledge. The models for the utilization and management of these resources may vary from community to community. The concept of CPRs user group is showing the best way of resource management in study area as well as Nepalese society which can fit well into increasingly emphasized grass root level for democratic decision-making, participatory development and fair equity distribution. This study shows that each community can develop and have to develop its own model in keeping with the local socio-economic and resource related circumstances. In this context, this study tries to investigate some of the existing resources and their management practices in the study area for the sustainable use and community development with the help of CPRs and suggests that the groups can be facilitated by providing legal flexibility and logistic support from the government instead of imposing any outsider model. Key words: Common Property; Sustainable management; Palpa Nepal Tribhuvan University Journal Volume XXVI No. 1, 2009 Page: 109-120